If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(1+v)(2v-7)=0
We add all the numbers together, and all the variables
(v+1)(2v-7)=0
We multiply parentheses ..
(+2v^2-7v+2v-7)=0
We get rid of parentheses
2v^2-7v+2v-7=0
We add all the numbers together, and all the variables
2v^2-5v-7=0
a = 2; b = -5; c = -7;
Δ = b2-4ac
Δ = -52-4·2·(-7)
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$v_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$v_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{81}=9$$v_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-9}{2*2}=\frac{-4}{4} =-1 $$v_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+9}{2*2}=\frac{14}{4} =3+1/2 $
| 4(z-7)-10=-58 | | R(p)=-1200p^2+330000p | | 5x^-4=25 | | 7=p/6+5 | | 0=93.5x+-39x2+4x3 | | 81=3c+6c | | 3z^2+45=18z | | 5b-2b=-27 | | 10=-3x+7 | | 5b–2b=-27 | | 3/2(2x+4)=2x-5 | | x+66+2x=180 | | 2/3(2x+4)=2x-5 | | 1/3(2x+4)=2x-5 | | 14=10+v2 | | (2x+4)=2x-5 | | 26-5z=43 | | x+(x+4)-(x-2)=224 | | 9(t–1)=-63 | | -13=x-6 | | x-(x+4)-(x-2)=224 | | x-(x+4)+(x-2)=224 | | 7-7.4x=1.5x-6 | | (2x+4)=4x-2 | | 2x(x^2+9)-100=0 | | x+(x+4)+(x-2)=224 | | X(x+6)=108 | | 4v-9=-37 | | -9-12=3y+12 | | 10n+3(3n+5)+23=× | | x+(x-4)+(x+2)=224 | | 3x3=6+ |